Adenoid Cystic Carcinoma of the Bartholin's Gland: A Diagnostic Dilemma. (18th August 2019) - Lo, Charmaine C. W.; Leow, Jerome B. Y.; Naing, K.; Jaaback, Ken; Thachil, Thanuja
Abstract : Adenoid cystic carcinomas of the Bartholin's gland are extremely rare and are often misdiagnosed. There are currently no definite treatment guidelines. This article describes the case of a 33-year-old female who was managed at our centre for adenoid cystic carcinoma of the Bartholin's gland. She presented with a prolonged history of a vulvar lesion which was eventually diagnosed as adenoid cystic carcinoma of the Bartholin's gland. She was subsequently treated with wide local excision of the primary and inguinal lymph node dissection followed by adjuvant radiotherapy and chemotherapy. She had gross perineural invasion on MRI imaging. The present case highlights the diagnostic dilemma in this extremely rare cancer and the literature further explores the natural history and treatment options.